Bioindicators and biomonitoring: Review of methodologies applied in water bodies and use during the Covid-19 pandemic - Serafín Muñoz, Alma Hortensia; Guerrero Aguilar, Armando; Rodríguez Castrejón, Ulises Emiliano; Schüth, Christoph; Noriega Luna, Berenice (Acta Universitaria, 2022)
The objective of this review is to highlight the importance of the use and application of bioindicators in the evaluation of the quality of water bodies from their origins to the present Era; during and post Covid-19 Era (2019-2022). More than 800 papers were analyzed in relation to the theme and the discussion of the advantages and disadvantages of the application of biomonitoring studies, criteria for selection of methods and organisms. This review focuses on algae, benthic macroinvertebrates and fish in river ecosystems, reservoirs, and other water bodies. Different types of biomonitoring methodologies are addressed, including biotic and diversity indices, multimetric and multivariate approaches, integrative methods, functional metrics, and new generation biomonitoring or "biomonitoring 2.0". This review highlights the great importance of the use and application of bio-indicators and biomonitoring techniques within environmental management and environmental health sustainably.